1992
DOI: 10.1152/ajprenal.1992.263.5.f894
|View full text |Cite
|
Sign up to set email alerts
|

Comparative sensitivities of isolated rat renal arterioles to endothelin

Abstract: The specific intrarenal sites and mechanism of endothelin (ET) vascular action are controversial. In this study afferent (AA) and efferent arterioles (EA) were isolated from the kidneys of normal Sprague-Dawley rats. Their respective concentration-dependent changes in lumen diameter in response to ET-1 were compared with those of angiotensin II (ANG II) and norepinephrine (NE). In a second series of experiments, the duration of vasoconstriction to comparable transient submaximal ET-1, ANG II, and NE concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The decrease in GFR may have been due to a predominant efferent arteriole vasodilation. This explanation is supported by several micropuncture 22 and in vitro microperfusion 23 studies that have found that efferent arterioles are more sensitive than afferent arterioles to ET administration. However, we again cannot rule out that changes in the ultrafiltration coefficient accounted for the changes in GFR, although this would be unusual, since most studies show either no change or decreased permeability during ET infusion.…”
Section: Relative Role Of Ang II Through Its At 1 Receptor Et No Amentioning
confidence: 75%
“…The decrease in GFR may have been due to a predominant efferent arteriole vasodilation. This explanation is supported by several micropuncture 22 and in vitro microperfusion 23 studies that have found that efferent arterioles are more sensitive than afferent arterioles to ET administration. However, we again cannot rule out that changes in the ultrafiltration coefficient accounted for the changes in GFR, although this would be unusual, since most studies show either no change or decreased permeability during ET infusion.…”
Section: Relative Role Of Ang II Through Its At 1 Receptor Et No Amentioning
confidence: 75%
“…Concentration response curves to increasing molar concentrations of ET were previously determined by our laboratory ( 16). Using known near maximal concentrations of ET for AA ( 10 -1 M) and EA ( 10-11 M), changes in lumen diameter with ET alone were compared to changes observed with ET in the presence ofthe putative ETA receptor antagonist (Cyclo D-Asp-L-Pro-D-Val-L-Leu-D-Trp; Peptides International Inc., Louisville, KY).…”
Section: Methodsmentioning
confidence: 99%
“…Presumably, the molecular radius of such an antibody was too large to permit significant extravascular movement into the subintimal or perivascular space suggesting its primary effect likely involved the binding of circulating ET. On the other hand, there is evidence that ET released from endothelial cells acts primarily by a paracrine mechanism, binding to receptors on adjacent smooth muscle cells ( 15,16). Theoretically, such a mechanism would not be affected by an anti-ET antibody with limited access to the subintimal space.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the renal vasculature appears particularly sensitive to the vasohonstrictor effects of endothelin (Pernow et al, 1988: Lanese et al, 1992, and ET-1 can be produced in several renal cell types (Kon & Badr, 1991;Perico & Remuzzi, 1993). Since several forms of acute renal failure involve intense renal vasoconstriction, it is not surprising that endothelin has been postulated as a potential mediator.…”
Section: Introductionmentioning
confidence: 99%